2008
DOI: 10.1111/j.1469-1809.2008.00440.x
|View full text |Cite
|
Sign up to set email alerts
|

Y‐Chromosome Analysis of Ancient Hungarian and Two Modern Hungarian‐Speaking Populations from the Carpathian Basin

Abstract: SummaryThe Hungarian population belongs linguistically to the Finno-Ugric branch of the Uralic family. The Tat C allele is an interesting marker in the Finno-Ugric context, distributed in all the Finno-Ugric-speaking populations, except for Hungarians. This question arises whether the ancestral Hungarians, who settled in the Carpathian Basin, harbored this polymorphism or not. 100 men from modern Hungary, 97 Szeklers (a Hungarian-speaking population from Transylvania), and 4 archaeologically Hungarian bone sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 48 publications
4
41
0
Order By: Relevance
“…In particular, concerning the real exception to our congruence pattern, notice that the presence in modern Hungarians of DNA markers currently common in Northern and Central Asia has been interpreted as a consequence of westward gene flow in Medieval times (Csányi et al, 2008; Bíró et al, 2009; Hellenthal et al, 2014); this is obviously connected with historical migrations in the 9th century and with the fact that the current language is closely related to the Ugric‐speaking communities along the Ob river. However, the current low frequency of those markers is not what one would expect to observe, had a substantial demographic replacement occurred (Nadasi et al, 2007; Hellenthal et al, 2014).…”
Section: Discussionmentioning
confidence: 74%
“…In particular, concerning the real exception to our congruence pattern, notice that the presence in modern Hungarians of DNA markers currently common in Northern and Central Asia has been interpreted as a consequence of westward gene flow in Medieval times (Csányi et al, 2008; Bíró et al, 2009; Hellenthal et al, 2014); this is obviously connected with historical migrations in the 9th century and with the fact that the current language is closely related to the Ugric‐speaking communities along the Ob river. However, the current low frequency of those markers is not what one would expect to observe, had a substantial demographic replacement occurred (Nadasi et al, 2007; Hellenthal et al, 2014).…”
Section: Discussionmentioning
confidence: 74%
“…In Europe, the Hungarians linguistically belong to the Finno-Ugric language family, but from the historical information, it is possible that during 1,000 years the ancient ethnic components of Hungarian populations could have changed as a result of admixture with other tribes. This has been investigated (Csanyi et al, 2008) by comparing the Y-chromosome markers among the two modern Hungarian-speaking populations and ancient Hungarian skeletal samples of 10th century. The results (high frequency of haplogroup J in both Szeklers and Hungarians) confirmed that modern populations are genetically closely related and are similar to populations from Central Europe and the Balkans.…”
Section: Association Between Genetic and Linguistic Boundariesmentioning
confidence: 99%
“…On the basis of multiple microsatellite loci, Belle and Barbujani (2007) examined the association between geography and language in shaping human genetic diversity among 52 world populations. At regional level, for example, in Europe, Y-chromosome markers have been used to examine the genetic affinity between two modern Hungarian-speaking populations (Csanyi et al, 2008), and the association between Y-chromosome diversity (Y-SNP) and linguistic affiliation of Austronesian-and Paupan-speaking communities in the Solomon Islands was also investigated (Cox and Lahr, 2006). Similarly, Hunley and Long (2005) found inconsistency between genetic structure (based on mitochondrial DNA diversity) and linguistic classification and also provided evidence of gene flow across linguistic boundaries among the native North American populations.…”
mentioning
confidence: 99%
“…Charlemagne's eastward expansion defeated them at the end of the eighth century, and partly replaced them by Bavarian and Slavic incomers. After the Hungarian Conquest of 895, the survivors were replaced or absorbed by the Hungarian tribes, pagan nomads from across the Carpathians, whose language and patrilineal ancestry can be traced back to the forest tribes living beside the river Ob in western Siberia (Csányi et al 2008).…”
Section: Introductionmentioning
confidence: 99%